METHODS OF TRAINING THE DEVELOPMENT OF PHYSICAL QUALITIES OF STUDENTS WITH A LOW LEVEL PHYSICAL FITNESS (American Journal of Pedagogical and Educational Research, 2023)
The article provides a theoretical and experimental justification of the methodology for training the development of physical qualities of students with a low level of physical fitness due to the selection of an individually optimal pace of motor actions and the standardization of physical activity in a given time period. The results of the experiment are presented, reflecting the effectiveness of individualization of training of secondary school students with a low level of physical fitness.